Effects of hypoxia exposure on human hippocampal astrocytes cultures - M. Nor Nazli , Nurul Atikah (2017)
The brain requires a continuous supply of oxygen to perform its normal function. Being the largest consumer of oxygen, it is especially sensitive to hypoxia, a condition in which brain receives reduced oxygen. Despite many animal studies reported that hypoxia caused neuronal damage in hippocampus which could deficits learning and memory, the exact damage caused by chronic hypoxia on human hippocampal astrocyte has not been analysed yet. Our aim for this study is to understand the characterization of human hippocampal astrocyte following hypoxia exposure and how the changes varied according to different concentration levels of oxygen. For the laboratory work, human hippocampal astrocytes cell line and hypoxia chamber were used in mimicking the hypoxic condition. Based on the preliminary screening, almost 80% of cell death occurred after 20 min and 60% cell death occurred in 15 min after exposed to chronic hypoxia, 3% of oxygen level (p<0.05). From the data gained, 15 minutes was chosen as the time point and the cells were exposed to different oxygen percentage.Analysis from Trypan blue viability assay showed about 15% of cells were dead in 15% oxygen, 25% dead cells in 10% oxygen, 48% dead cells in 5% oxygen and 65% dead cells in 3% oxygen (p<0.05). For the immunofluorescence assay, a reliable marker Glial Fibriallary Acidic Protein (GFAP) was used in order to portray the architecture and morphology of astrocytes cells. Fluorescence scanning microscope revealed a filamentous and clear nucleas appearance in a control. In contrast, the rupture nuclei along with no rigid structure of cell were displayed in chronic hypoxia group, the 3% oxygen exposure. The expression of GFAP among the five groups showed different intensity of GFAP. The significant different of the mean intensity was clearly showed in the chronic hypoxia group (pvalue<0.001). Along with that, the HIF-1 staining was performed to confirm the cell death due to hypoxia exposure. Based on the fluorescence microscope viewed, different expression of HIF-1α were displayed in all exposed astrocyte cells (p-value<0.001). In the molecular analysis using RTPCR, there were significant changes of GFAP and HIF-1α in chronic hypoxia exposed cells when compared to control and acute hypoxia exposed cells (p-value< 0.05). To conclude, changes of the morphology of astrocyte cells are seen after 15 exposed to chronic hypoxia, 3% oxygen.